Genomic signatures of domestication and adaptation during geographical expansions of rice cultivation - Zheng, Xiaoming; Pang, Hongbo; Wang, Junrui; Yao, Xuefeng; Song, Yue; Li, Fei; Lou, Danjing; Ge, Jinyue; Zhao, Zongyao; Qiao, Weihua; Kim, Sung-Ryul; Ye, Guoyou; et al. (Wiley, 2022)
Rice (Oryza sativa L.), a global staple food now grown on all inhabited continents, was domesticated from its wild progenitor, O. rufipogon Griff., in tropical and subtropical regions of Asia (Oka, 1988). After domestication, the expansions of rice landraces into the present-day range required a diverse array of adaptations to local environments, which included changes in daylight sensitivity, expanded thermal tolerance (for excess cold and heat), adaptations to water availability (drought and waterlogging), and resistance to biotic stresses (Garris et al., 2005; Glaszmann, 1987). Although a large amount of genomic data has been available for wild and cultivated rice varieties, and genetic characterizations of important agronomic traits were obtained in the past two decades (Gutaker et al., 2020; Huang et al., 2011, 2012; Wang et al., 2016), a complete landscape of genomic variations underlying regional adaptations remains elusive.